2001
DOI: 10.1046/j.1464-4096.2001.01653.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary stress incontinence in obese women: tension‐free vaginal tape is the answer

Abstract: Objective To determine the effectiveness of the tensionfree vaginal tape (TVT) in obese women with genuine stress incontinence (GSI), in whom obesity is often considered a relative contraindication to surgical treatment by traditional approaches, e.g. Burch colposuspension and slings (which are dif®cult and carry increased morbidity) or injectable agents (which although simple, are unpredictable and expensive). Patients and methods Data on 242 consecutive women with urodynamically proven GSI were collected pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
1
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 12 publications
3
36
1
5
Order By: Relevance
“…Some of these studies revealed no difference in the potential impact of obesity on TVT outcomes in shortterm follow-up (<1 year). [21][22][23] On the other hand, Hellberg and colleagues reported significant failure rates (52%) in the severely obese population (BMI >35) compared to non-obese women (19%) with long-term follow-up (mean 68 months). 24 Although TVT is a good option for severely obese patients with severe incontinence, TOT has become an acceptable alternative in the surgical treatment of SUI.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies revealed no difference in the potential impact of obesity on TVT outcomes in shortterm follow-up (<1 year). [21][22][23] On the other hand, Hellberg and colleagues reported significant failure rates (52%) in the severely obese population (BMI >35) compared to non-obese women (19%) with long-term follow-up (mean 68 months). 24 Although TVT is a good option for severely obese patients with severe incontinence, TOT has become an acceptable alternative in the surgical treatment of SUI.…”
Section: Discussionmentioning
confidence: 99%
“…In the prospective study conducted by Mukherjee et al [25] with 242 women who underwent SUI surgery, they divided these women into three groups according to their BMI and determined no difference between the rates of wound site infection and retropubic hematoma in the obese group.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported high cure rates of 78.9% to 84.7% after long-term follow-up [15,16] and described relatively low intraoperative and postoperative complication rates [17]. However, there are few published short-term studies on the outcomes of the TVT procedure in overweight and obese women [13,[18][19][20]. Chung et al retrospectively compared the efficacy and safety of 91 cases of TVT procedures and 51 laparoscopic Burch procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Given the finding of fewer complications, the authors suggested that this procedure might be an ideal surgical treatment modality for USI in obese women [13]. Mukherjee and Constantine [19] compared the data of 242 women who underwent the TVT procedure with a follow-up of 6 months. The cure rate was 85% in women with BMI <25, 95% in women with BMI 25-29, and 89% in women with BMI >30.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation